Burden of postinfectious symptoms after acute dengue, Vietnam - Tam, DTH; Clapham, H; Giger, E; Kieu, NTT; Nam, NT; Hong, DTT; Nuoi, BT; Cam, NTH; Quyen, NTH; Turner, HC; Jaenisch, T; Simmons, CP; et al. (Centers for Disease Control and Prevention, 2022)
We assessed predominantly pediatric patients in Vietnam with dengue and other febrile illness 3 months after acute illness. Among dengue patients, 47% reported >1 postacute symptom. Most resolved by 3 months, but alopecia and vision problems often persisted. Our findings provide additional evidence on postacute dengue burden and confirm children are affected.